The Relationship Between Perceived Benefits With Implementation Of Household Clean And Healthy Lifing Behaviors During The Covid-19 Pandemic - Yusriani Yusriani; Andi Asrina; Dwi Murty Wardani Hermanzah (Jurnal EduHealth, 2023)
Covid-19 was designated by WHO as a global pandemic in March 2020, for this reason the government issued policies, promotive and preventive services, in this case, calling for the implementation of Clean and Healthy Life Behavior (PHBS) including household. PHBS itself has not been fully implemented in the community, if you refer to this that health problems in the community are caused by habits and perceptions, this is expressed by Rosenstock regarding the Health Belief Model, especially perceived severity. Based on data from the Maros District Health Office in Simbang District, the coverage of PHBS is 25% and those who have not PHBS are 75%. This study aims to determine the relationship between the perceived benefit approach and the application of household PHBS during the Covid-19 pandemic in the community of Simbang Village, Maros Regency. The research method used is a quantitative study with a cross-sectional design. The population in this study is the community in this case housewives who have babies/toddlers totaling 290 people. Sampling by purposive sampling method with a total of 166 people. The data analysis method used a bivariate test with a Chi-Square correlation test. The results showed the results of the Chi-Square test variable perceived benefit (p-value 0.192). Based on the results of the study, it was concluded that there was no relationship between the perception of benefits and the application of household PHBS, which was due to other factors that dominated the community in implementing household PHBS during the Covid-19 pandemic.